Magnetic anisotropy and stability of Fe3Ga compounds - Inerbaev, T; Abuova, A.U.; Dauletbekova, A.K.; Abuova, F.U.; Kaptagay, G.A.; Zakieva, Zh.; Eltizarova, M.; Barakov, A. (Eurasian Journal of Physics and Functional Materials, 2026)
The magnetic anisotropy energy and the stability of crystal modifications of D03 and L21 of Fe3Ga compounds are studied with the density functional theory methods. The magnetic anisotropy energy of the D03 structure is more than twice the same value for the L21 structure. The features in the electronic structure lead to the difference in the magnitude of spin-orbit interaction, explaining the found effect. The L21 structure is more thermodynamically stable in the entire range of the considered pressures. Under pressure, the considered crystal modifications of Fe3Ga lose their stability due to the appearance of imaginary frequencies in their phonon spectra. © 2021. All Rights Reserved.Recommended CitationInerbaev, T. M.; Abuova, A. U.; Dauletbekova, A. K.; Abuova, F. U.; Kaptagay, G. A.; and Zakieva, Z. (2021) "Magnetic anisotropy and stability of Fe3Ga compounds," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 4, Article 7.DOI: https://doi.org/10.32523/ejpfm.2021050407